Instating settings of emergency education in Vienna: temporary schooling of pupils with forced migration backgrounds. Issue 2 (28th January 2021) - Proyer, Michelle; Biewer, Gottfried; Kreuter, Linda; Weiß, Jekaterina
ABSTRACT: In the year 2015, Austria was one of the main European destinations of displaced persons. According to education authoritiesaround 15, 000 children with a forced migration background of school age who arrived in Austria over the course of a few months from late2015 to the beginning of 2016 called for immediate and partly temporary solutions. Due to Austrian legislation and unlike other countries, every child living in Austria between the ages of six to fifteen (or for nine years of schooling) is entitled to receive compulsory education. Though the school administration of Vienna generally promotes an inclusive approach to education in regular schools, schools inneighbourhoods with a large refugee population were reportedly unable to provide appropriate and adequate education for all children. Inresponse, the local school authority in Vienna decided to establish temporary classrooms in refugee accommodations. This article describesand analyses the emergence of new educational structures from the point of view of university students and lecturers who took part in theone and a half years of its implementation. The article thereby aims to document specific perspectives on educational emergency measuresat a certain point of time. In both the primary and secondary sectors, the emergence of a new temporary field of specialised and exceptional education were observed and recorded in a thick description of dynamic processes of trans-institutional, trans-organisational, transprofessional, communal, and individual development. Thus, the article presents a multifaceted picture of problems in refugee education under exceptional circumstances. The findings illustrate how insufficient educational opportunities for those falling outside the age of compulsory schooling – in particular, preschool children as well as youth older than fifteen – diminish possibilities for the inclusion of these children within and beyond education.